Effect of drying and grinding or micro-grinding process on physical and rheological properties of whole cladode (Opuntia ficus-indica) flour. (November 2021) - Chaloulos, Panagiotis; Bazanis, Apostolos-Emmanouil; Georgiadou, Maria; Protonotariou, Styliani; Mandala, Ioanna
Abstract: Cactus ( Opuntia ficus-indica ) cladodes are a source of dietary fiber, vitamins and antioxidants that could be utilized by the food industry for both their nutritional and technological properties. In the present study, cladodes were dried at 45°C for 24 h, followed by a 18 h vacuum drying at 45°C or 60°C. The dried cladodes were then ground in a grain mill, resulting in two coarse cladode flours (C45 and C60, respectively). A portion of the two flours was further ground with jet mill, yielding two fine flours, J45 and J60, respectively. Color, bulk density, water and oil holding capacities, solubility and dietary fiber content were determined. In addition, rheological properties and sedimentation kinetic of aqueous cladode flour suspensions were evaluated. An increase of insoluble fiber was observed with micro-grinding. All samples exhibited shear thinning behavior, while jet milling led to substantial decrease in apparent viscosity values. Coarse fractions sedimented quickly, achieving almost maximum sedimentation within 10 min, while the micro ground samples sedimented half as fast. In conclusion, particle size significantly alters the technological properties of cladode flour, broadening the range of applications cladodes could be used for. Highlights: Cactus ( Opuntia ficus-indica ) cladodes whole flour successful production. Drying temperature increase diminishes the particle size of cladode flours. Coarse grinding results of higher density, darker particles of uneven size and shape. Microgrinding increases the insoluble:soluble fibers ratio in cladode flour. Microgrinding decreases viscosity and pseudoplasticity of cladode flour suspensions.